Podstawy Teorii Bezpieczeństwa Konstrukcji - Eimer, C. (Engineering Transactions, 1963)
This paper discusses in a synthetic manner the whole of the fundamental problems of the theory of safety of structures and is intended for readers who want to make themselves acquainted with the most important elements of this theory and to have an insight into the essentials of the problem. The durable achievements of the theory are discussed. The paper contains also a critical survey of the evolution of the existing notions and is completed with a number of original results.The following topics are discussed: Existing theories and their evolution, a number of inaccuracies of various authors being corrected; The economic sense of the problem; Basic notions and relations, in particular the structure of the safety condition; Theory of conventional measures of safety (admissible stresses); The problem of loads, especially an analysis of their probability distribution; Practical computation with homogeneous distributions of most important types: normal, logarithmic-normal, and Pearson. Approximate methods based on linearization, transformation of the distributions and application of critical quantities, The argument is completed by a list of the most important literature on the subject.